An enhanced voice based chatbot using artificial intelligence - Saratha Devi, G; G, Vinothini; Devi.C, Janani; C, Jeyachandrakala (International Journal of Engineering and Technology, 2017)
The chatbot application developed using various programming languages with user interface to send input and receive response contains certain boundaries and limitations. This paper proposes a chatbot application for assisting the information regarding the colleges with the use of artificial intelligence. This system has been embedded artificial intelligence to help the user to resolve the questions by providing a human way interactions to identify the sentences and making a decision itself as response to answer a question overcoming the use of programming languages.